Environmental Catastrophe in Amitav Ghosh’s The Hungry Tide - Ahmad, Zahra; Rehana, Shahla (International Journal of Language and Literary Studies, 2024)
“Conservation is a state of harmony between men and land. Despite nearly a century of propaganda, conservation still proceeds at a snail’s pace; progress still consists largely of letterhead pieties and convention oratory. … we still slip two steps backward for each forward stride.” (Leopold, 1968, p. 207) Since time immemorial men have ruled nature, escalated environmental issues and caused irreparable losses, posing a threat to their very own survival. Due to the negligence and degradation of the ecosystem, environmental concerns have become a global crisis. Aldo Leopold, Wangari Maathai and Rachael Carson are some of the prominent activists who raised their voices for the protection of nature. Amitav Ghosh in his novel The Hungry Tide set in the Sundarbans, meaning beautiful forests, emphasises the understanding and conservation of life in the Sundarbans, depicting a global issue in a local setting. The novel deals with the wrath of nature and colonial suppression. This paper intends to depict the environmental issues of the Sundarbans faced by its human and non-human inhabitants as well as bring out the human and environmental relationships in the novel. It also seeks to depict natural and manmade calamities in this rare ecologically rich biodiversity and the clarion call given by the author to save the environment.